Concomitant cellular and humoral expression of a regulatory cross-reactive idiotype in acute Schistosoma japonicum infection. - Kresina, T F (Infect Immun, 1986)
In this study the expression of a regulatory cross-reactive idiotype (SJ-CRIM), which is associated with anti-soluble egg antigen (SEA) molecules in murine Schistosoma japonicum infection, is described. Both humoral and cellular components of the immune response were analyzed during the course of infection with S. japonicum. In the humoral immune response, the content of SJ-CRIM decreases as the titer of anti-SEA antibody increases throughout infection. Quantitatively, values for serum ranged from 13.8 +/- 0.3 micrograms of SJ-CRIM, which binds anti-idiotypic antibody per ml of serum at 6 weeks postinfection, to 1.3 +/- 1.8 micrograms/ml at 30 weeks postinfection. Analysis of splenic cell subpopulations for expression of SJ-CRIM revealed that only splenic B cells expressed SJ-CRIM during acute infection (5 to 10 weeks postinfection). On the other hand, thymic cells with a high expression of the SJ-CRIM and Ly-1 marker were observed in acute infections up to 15 weeks postinfection. These data indicate that SJ-CRIM-bearing T cells are selectively localized in acute infection. In addition, the disappearance of expression of SJ-CRIM in serum and cells of chronically infected animals parallels the modulation of granulomatous inflammation and portal hypertension. Results of this study suggest that expression of SJ-CRIM on anti-SEA molecules could represent a marker for acute infection, while its disappearance from serum serves as a marker for modulation of disease.